Axial control of protein reserve mobilization during germination of indian bean (Dolichos lablab L.) seeds - Ramakrishna, Vadde; Ramakrishna, Rao Pillatla (Acta Biologica Szegediensis, 2005)
The influence of embryonic axis and exogenously applied plant growth hormones on protein mobilization and development of proteases have been investigated in Indian bean (Dolichos lablab L. var lignosus) seeds during germination and post-germinative growth up to 10 days. Accumulation of free amino acids synchronized with rapid proteolysis and higher levels were maintained throughout the germination period. The presence of proteases (acid, neutral and alkaline) with three different pH optima increased in the early stages of germination and decreased later. The axis-excision affected the activities of proteases and protein degradation. Furthermore, the free amino acid content increased continuously in detached cotyledons throughout the germination period. Treatment with 1% casein hydrolysate to simulate the accumulation of free amino acids had a telling inhibitory effect on the proteases in attached and detached cotyledons. Exogenously applied phytohormones BA (Benzyl adenine), GA3 (Gibberellic acid) or IAA (Indole acetic acid) resulted in stimulation of development of proteases as well as proteolysis in detached cotyledons. The two hypotheses, source-sink and hormonal stimulus both were influencing in the mobilization of food reserves and the growth of seedling. The results of the study supports the role of axis in protein mobilization regulating the development of proteases by providing phytohormone signals and regulation of their activity in vivo by a feedback mechanism.